Examination of Student’s Motivation to Participate in E-Sport - Tóthné Kovács, Enikő; T. Kiss, Judit (International Journal of Engineering and Management Sciences, 2019)
The basis of our research is the popularization of e-sport and its significant development. Compared to many other sports, e-sport is not only a sports game, it is also a dynamically developing business in which the market success of its stakeholders depends to a large extent on its ability to recognize the needs of its stakeholders, sportsmen, the public and sports clubs. In our research we are looking for the answer to the question of students' attitude towards e-sports and what motivates them to spend more time with e-sports. Among other things, we have found that students are intrinsically motivated, besides getting their own pleasure, meeting themselves, it is very important to gain experience and to constantly develop themselves, to learn more new techniques and methods with the given e-sports game.